The role of oil prices and the real exchange rate in Russia's economy - Jouko Rautava (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
Most people seem to think that Russia's economy and fiscal situation are still crucially tied up with international oil prices and the exchange rate of the rouble, although this view has recently been challenged by some analysts.Empirical research on this topic is, however, scanty.In this paper, the impact of international oil prices and the real exchange rate on Russia's economy and fiscal policy is analysed using VAR methodology and cointegration techniques.The research period covered is 1995:Q1 - 2001:Q3.The results indicate that in the long run a 10% permanent increase (decrease) in international oil prices is associated with a 2.2% growth (fall) in the level of Russian GDP.Respectively, a 10% real appreciation (depreciation) of the rouble is associated with a 2.4% decline (increase) in the level of output.These long-run equilibrium relationships also have a significant impact on short-run dynamics through an error-correction mechanism.The estimation results confirm also a strong dependence of fiscal revenues on output and oil price fluctuations.Estimated parameters and diagnostic statistics do not indicate that Russia's dependence on oil and the real exchange rate would somehow have weakened in recent years.
URN:NBN:fi:bof-201408072172
Keywords: 330; Russian economy; fiscal policy; oil; real exchange rate; VAR; cointegration